A study on the teachers’ teaching techniques for improving the reading skills of freshmen at Hanoi College of Industrial Economics: . M.A Thesis - Đặng, Thúy Hằng (ĐHNN, 2017)
M.A. Thesis -- ĐHNN. Vietnam National University, Hanoi, 2014